Process-based approach to teaching written English to first-year university students in Lebanon: an exploratory study - Ali, Hisham A. (University of Edinburgh, 1988)
This thesis reports the results of an investigation into the effects of an experiment in the teaching of written composition in English as a foreign language based on the findings of so-called 'process-related' research over the last 17 years in both mother tongue and foreign language contexts. The experiment was conducted at Beirut University College during the 1986-1987 Fall semester,, with 52 firstyear students controlled for age, sex, and initial English language writing ability as evidenced through a pre-test. The experiment continued for 70 periods of instruction over 14 weeks, five periods per week. Pre- and post-tests were graded by the same judges (native-speaking teachers of English as a foreign/second language or students of applied linguistics). The results revealed that the performance of the subjects in the experimental (process) group was significantly better than that of the subjects in the control (product) group. It is hypothesized that the-superior performance of the experimental group may be attributed (at least in part) to the following components of the 'process approach': (1) writing as a meaning-creating activity, i.e. learners see their writing as a way of expressing their own ideas and opinions; (2) reading for writing, i. e. learners extract and assimilate the meanings derived from what they read and use that as an input to their own writing; (3) speaking for writing, i. e. learners negotiate their own and the extracted meanings with the peer group and with the teacher; and (4) multi-drafting, i. e. drafting followed by revision on the basis of pointed feedback from the teacher and self-reflection. The thesis concludes that a writing instruction programme characterized, inter alia, by the above features will be more successful than conventional 'product-based' writing pedagogy. The thesis also suggests directions for further research into the individual contribution of the above components.
A process-based approach to teaching written English to first-year university students in Lebanon: an exploratory study
Keywords: Linguistics; Education